Effect of image‐matching parameters and local morphology on the geomorphological quality of SPOT DEMs. (10th August 2017) - El Hage, Mhamad; Simonetto, Elisabeth; Faour, Ghaleb; Polidori, Laurent
Abstract: Digital elevation models (DEMs) are used for many applications, including geomorphological feature identification. This study assesses, for selected regions of Lebanon, the impact of matching parameters on the geomorphic indices extracted from photogrammetrically derived DEMs. Three parameters are shown to have a significant effect on the geomorphic indices: the template size and the correlation and curvature thresholds. The most influential parameter is the template size, an increase in which decreases the proportion of interpolated points and leads to more reliable matching, but it also tends to smooth the morphology of the DEM. A small template size tends to preserve the details of the terrain, especially for steep slopes, but it also increases noise in the DEM. For the present study, the optimal value for this parameter is about 13 × 13 pixels. High threshold values lead to more reliable matches but also increase the proportion of interpolated points, which has a significant effect on the resulting geomorphology.